2020
DOI: 10.1002/asia.201901647
|View full text |Cite
|
Sign up to set email alerts
|

KOtBu‐Catalyzed Michael Addition Reactions Under Mild and Solvent‐Free Conditions

Abstract: Designed transition metal complexes predominantly catalyze Michael addition reactions. Inorganic and organic base‐catalyzed Michael addition reactions have been reported. However, known base‐catalyzed reactions suffer from the requirement of solvents, additives, high pressure and also side‐reactions. Herein, we demonstrate a mild and environmentally friendly strategy of readily available KOtBu‐catalyzed Michael addition reactions. This simple inorganic base efficiently catalyzes the Michael addition of underex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…As another example, our group described that a copper catalyst could control the selectivity of the aza‐Michael addition of indole to vinyl sulfones, providing the desired β ‐indole‐substituted sulfones in high efficiencies [10] . During our studies, Gunanathan and co‐workers reported that KO t ‐Bu could selectively catalyze the conjugate addition of azoles, including an indole, to α , β ‐unsaturated nitriles under mild reaction conditions [11] . Although these reported reactions are highly regio‐ and chemoselective, a number of drawbacks should be addressed to improve their synthetic utility.…”
Section: Introductionmentioning
confidence: 92%
“…As another example, our group described that a copper catalyst could control the selectivity of the aza‐Michael addition of indole to vinyl sulfones, providing the desired β ‐indole‐substituted sulfones in high efficiencies [10] . During our studies, Gunanathan and co‐workers reported that KO t ‐Bu could selectively catalyze the conjugate addition of azoles, including an indole, to α , β ‐unsaturated nitriles under mild reaction conditions [11] . Although these reported reactions are highly regio‐ and chemoselective, a number of drawbacks should be addressed to improve their synthetic utility.…”
Section: Introductionmentioning
confidence: 92%
“…For example, addition product 1c has been obtained in 93% conversion before using 10 mol % TPP, 3 equiv c and heating the reaction mixture for 8 h under refluxing conditions [14]. However, with base catalysis (KOt-Bu) even better results than those presented here can be achieved [22,23].…”
Section: Resultsmentioning
confidence: 67%
“…Products 36 and 27 are transformed to the corresponding lactone products 92 and 93 in 80%, and 66% yields, respectively (Scheme c­(i),(ii)). In addition, δ-hydroxynitriles 25 and 21 underwent the Michael addition reaction to provide products 94 and 95 in very good yields (Scheme c­(iii),(iv)) …”
Section: Resultsmentioning
confidence: 99%